Answer :

We have


and


where x≠0 and y≠0


Lets simplify these equations. Assuming 1/x = p and 1/y = q, we can rewrite them,



3p – q = - 9 …(i)



2p + 3q = 5 …(ii)


To solve these equations, we need to make one of the variables (in both the equations) have same coefficient.


Lets multiply eq.(i) by 3, so that variable q in both the equations have same coefficient.


Recalling equations (i) & (ii),


3p – q = - 9 [×3


2p + 3q = 5



11p = - 22


p = - 2


Substitute p = - 2 in eq.(i)/eq.(ii), as per convenience of solving.


Thus, substituting in eq.(i), we get


3( - 2) – q = - 9


- 6 – q = - 9


q = 9 – 6


q = 3


Thus, p = - 2 and q = 3


As p = 1/x,


- 2 = 1/x


x = - 1/2


And q = 1/y


3 = 1/y


y = 1/3


Hence, we have x = - 1/2 and y = 1/3


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve each of theRS Aggarwal - Mathematics

If 2x – 3y = 7 anRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics